Edukasi Sertifikasi Halal Self-Declare bagi Pelaku UMKM: Membangun Wirausaha Halal di Kecamatan Kadungora, Garut - Malik Akbar Abdul Aziz; Rakhman Firdaus (GUYUB: Journal of Community Engagement, 2025)
This community service program was initiated in response to the low halal certification rate among food-sector MSMEs in Kadungora District, Garut Regency, where only 11.9% of active enterprises were certified. Amid the legal obligation mandated by Indonesia’s Law No. 33 of 2014 on Halal Product Assurance and the growing domestic and international demand for halal products, this intervention was designed to address key barriers such as low literacy, limited access, and technical challenges—particularly within the self-declare certification scheme. The program employed a Participatory Action Research (PAR) method, engaging MSME actors as key agents of change through two strategic stages: entrepreneurship seminars and intensive technical mentoring by certified Halal Product Process Assistants (PPH). The program outcomes indicate a significant increase in participants’ understanding of halal certification urgency, with Likert-scale scores rising from 2.3 to 4.5, and successful facilitation of certification for 25 MSMEs within 20 working days. Post-program monitoring revealed that 18 MSMEs integrated into digital platforms, achieved an average revenue increase of 20%, and received inquiries from local distributors, alongside early-stage export orientation toward markets in Malaysia and Singapore. The implications of this initiative demonstrate that a systematic education-and-assistance approach can serve as a replicable national model to enhance the competitiveness of MSMEs in the halal industry ecosystem and support Indonesia’s vision of becoming a global halal economic hub.